Model Kepemimpinan Transformasional Kepala Sekolah Perempuan dalam Meningkatkan Kualitas Pendidikan di Kota Mataram: Study Kasus di SD Negeri 13 Ampenan - Agus Mulianto; Yudin Citriadin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by the lack of research that addresses themes related to the leadership model of female school principals in improving the quality of education. This research aims to find out: (1) The leadership model of female school principals in improving the quality of education; (2) The implications of the transformational leadership of female school principals in improving the quality of education. This research uses qualitative research where this research focuses on individuals within the agency, namely the female principal at SD Negeri 13 Ampenan. The approach used in this research is a case study approach. . This type of case study research is research that is to be carried out against different backgrounds such as different levels, organizational characteristics, programs, economic backgrounds and socio-cultural backgrounds. Based on research results, SDN 13 Ampenan, Mataram City, is an educational institution that always gets a very good title. Starting from academic and non-academic achievements, in the fields of science, sports, arts and the environment. SDN 13 Ampenan Mataram City is also designed as a superior school, this goal is in accordance with the vision and mission which wants to become a school that has a vision of Smart, Skilled and Devoted Based on Faith, Knowledge and Charity. The leadership model applied by female school principals is a transformational leadership model. With this leadership model, it is hoped that it will be able to improve the quality of education at SDN 13 Ampenan, Mataram City and this can be additional new evidence that general assumptions that are discriminatory against women in matters of leadership in the educational environment seem to need to be dismantled immediately. Apart from that, the transformational leadership of female school principals is able to compete with male principals, so that the leadership of female school principals can show the same leadership results as men. This result can be seen from how a female school principal who has high integrity is able to provide strong motivation to teachers, especially in improving learning. Apart from that, a female school principal is also able to encourage the creativity of all stakeholders to have their own abilities and experiences.